Synthesis of oil palm empty fruit bunch (EFB) derived solid acid catalyst for esterification of waste cooking oils - Koguleshun S.; Fei-Ling P.; Nabihah S.; Chin-Hua C.; Shamala G. (Penerbit Universiti Kebangsaan Malaysia, 2023)
acid; biofuel; biomass; catalyst; fatty acid; Malaysia; Elaeis